Nano-polymeric curing agents for enhancing water stability in sandy soils: A sustainable approach for ecological slope protection - Shanshan Zhao; Aijun Chen; Xiong Shi; Zheng Li (PLoS ONE, 2025)
The susceptibility of sandy soil slopes to erosion, particularly during rainfall events, poses significant challenges for soil conservation and ecological slope protection. This study explores the potential of nano-polymeric curing agents (NPCA) as a sustainable solution to enhance water stability and slope integrity. Reinforcement depth experiments were conducted to determine the optimal application depth of NPCA, while permeability and erosion tests assessed its impact on water retention and soil stability. Advanced analytical techniques, including scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR), were employed to examine the interactions between NPCA and soil particles. Results show that a 3% NPCA content (mass ratio) achieves the maximum reinforcement depth of 23 mm. Within the optimal reinforcement range (mass ratio < 3%, concentration < 17%), increasing NPCA content enhances soil permeability, reduces the disintegration coefficient, and improves erosion resistance. NPCA encapsulates soil particles, filling pore spaces and binding them through van der Waals forces and hydrogen bonds, forming a durable, elastic membrane that enhances surface stability and water resistance. These findings suggest that NPCA treatment creates a stable, permeable, and breathable environment, crucial for promoting vegetation growth on sandy slopes and offering an effective, sustainable approach to ecological slope protection.